THE GERMAN ENERGY TRANSITION AND ITS STUMBLING BLOCKS—PROMOTION OF POWER GENERATION FROM PHOTOVOLTAIC SYSTEMS AND ITS INFLUENCE ON THE GERMAN ENERGY TRANSITION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The energy transition that began in Germany in 2000 is widely accepted by the population. Opinion research institutes report that more than 90 per cent agree with the policy adopted. Nevertheless, in the public debate in recent years increasingly critical opinions were voiced. In particular, the increased costs of the energy transitin are discussed, which are to be borne by the population and the economy. Despite increased burdens in all areas of the energy transition, the criticism is mostly due to the increased burden on electricity customers through the increased use of renewable energy. One reason for this is the increase in the Renewable Energy Act (EEG / Erneuerbare-Energien-Gesetz) surcharge, which finances the expansion of renewable energies and which ultimately has to be borne by the customers of the energy supply companies. This surcharge increased by 74 per cent in the years 2012 to 2014 alone. One of the main reasons for this was the excessive subsidization of electricity from photovoltaic systems from 2008 to 2012, which was primarily used by major investors and resulted in a massive expansion. Although the share of renewable energies in the German electricity mix has thus increased, an economic equivalent, such as a sustainable increase in jobs or high export figures among the companies that produce these plants, was not observed. Today, economists ask to what extent this mistake could have been avoided and to what extent this has damaged the reputation of the energy transition. The economic policy debate on this issue is led by various interest groups whose opinions are widely divergent. Establishing public consensus is difficult, yet essential for a successful continuation of the energy transition.